Peran Senam Ergonomis Untuk Kesehatan - Alfia Nurul Fatiha; Isa Ma'rufi; Dewi Rokhmah (Pascasarjana Universitas Jember, 2021)
The higher life expectancy of a country leads to a high number of elderly people followed by high health problems in the elderly both physically and psychologically. One of the efforts to suppress all complaints to the elderly is to do ergonomic gymnastics that has been proven to provide many benefits, especially to the elderly. Ergonomic gymnastics is a gymnastics that can directly open, clean, and activate the entire body systems such as cardiovascular, urinary, reproductive systems. These movements also allow the body to be able to control, ward off some diseases and malfunctions so that the body remains healthy. Literature search from February 2019 to June 2019 using the keywords